The introduction and current status of the multidimensional model of pain neurobiology - Casey, Kenneth L. (Frontiers in Pain Research, 2023)
Conceptual models are useful because they guide our practical actions related to whatever is represented by the model; this includes research that reveals the limitations of these actions and the potential for their improvement. These statements apply to many aspects of daily life and especially to pain as a challenge for both clinical practice specifically and neurobiology generally. In the first half of the 20th century, our conceptual model of pain, to the extent that it existed at all, was based on evidence supporting the proposition that pain emerged from activity within a very spatially limited set of central nervous system (CNS) structures located within the cerebral cortex and it's oligosynaptic connections with the thalamus. This CNS activity was strongly associated with the activation of physiologically distinct and specialized somatovisceral afferent fibers. All, or nearly all, aspects of the pain experience were thought to arise from, and be modified by, changes in that localized CNS activity. There was no compelling and widely accepted reason to consider an alternative model. However, neurophysiological, neuroanatomical, behavioral, and clinical evidence emerging in the late mid-20th century prompted a reconsideration of the prevailing model of pain neurobiology. Based on this new evidence and the perceived limitations of the prevailing model, pain could then be reasonably conceived as a multidimensional experience arising from the conjoint activation of physiologically and anatomically distinct but interacting CNS structures each separately mediating sensory discriminative, affective, and cognitive aspects of pain. This brief historical review describes the intellectual climate at the time this multidimensional model was proposed, the dispositions for resisting or accepting it, and concludes with a comment on the current status of the model as a fusion of distributed activations that create a unified perception of pain.